Structural, Optical and Photocatalytic Properties of Cerium Oxide Nanoparticles - Anbuvannan Mari; Maria Vinosel Vincent; Dhatshanamurthi Pachiyappan; Ramesh Mookkaiah; Uvarajan Sambath (Nanochemistry Research)
Sphere-like cerium dioxide nanoparticles were synthesized by a hydrothermal method. The resulting samples were investigated using various techniques, including X-ray powder diffraction spectroscopy (XRD), high-resolution scanning electron microscopy (HRSEM), energy dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), and ultraviolet visible absorption spectroscopy (UV-Vis spectra). The crystal structure of cubic fluorite and its average particle size range between 10- 20 nm, as determined by X-ray diffraction analysis. The diameters of the cerium dioxide nanoparticles in the range of 23.52 nm were determined using high-resolution scanning electron microscopy. Transmission electron microscopy revealed that the cerium dioxide nanoparticles were spherical with a diameter of approximately 15.3 nm. Energy-dispersive X-ray spectroscopy revealed highly pure cerium dioxide nanostructures. The bandgap energy of the cerium dioxide sample was estimated at 3.34 eV by ultraviolet-visible absorption spectroscopy. Moreover, the maximum photocatalytic activity and maximum photodegradation efficiency of Congo red dye were achieved by the action of valence band holes.